Risk factors of postoperative respiratory complications - Osmany Cruz García; Carlos Gilberto Nieto Monteagudo; Lester Álvarez Hurtado; Yassel Cruz Hernández; Marlon Cruz Hernández; Gretter Elena Nieto Martínez (Acta Médica del Centro, 2022)
Introduction: postoperative respiratory complications increase morbidity and mortality, hospital stay and health care costs. Objectives: to identify the incidence and risk factors for post-surgical respiratory complications. Methods: an observational, anality, cross-sectional study was conducted in 1 650 patients at the “Celestino Hernández Robau” Hospital between January 2018 and December 2019. The variables sex, age, weight, height, body mass index, smoking, alcoholism, physical status classification, type of anesthesia, type of surgery according to elective or urgent, type of surgery according to surgical location and time, nasogastric tube, hemoglobin level, albuminemia and preoperative oxygen saturation were evaluated and post-surgical respiratory complications were determined. Results: 5.15% of the patients presented postoperative respiratory complications and the frecuence of these complications was 6.72%. Risk factors were identified as age equal to or older than 68 years, smoking, physical status classification III and IV, endotracheal general anesthesia, surgical time longer than three hours, urgent, upper abdominal and head and neck surgery, hemoglobin levels less than 10 g/L, albumin levels less than 34 g/L, use of nasogastric tube and preoperative oxygen saturation equal to or less than 92%. Sex, body mass index and alcoholism were not related to an increase in respiratory complications. Conclusions: the association of risk factors increased the number of patients with postoperative respiratory complications.